2021
DOI: 10.1021/acsami.0c22831
|View full text |Cite
|
Sign up to set email alerts
|

Achieving the Super Gas-Wetting Alteration by Functionalized Nano-Silica for Improving Fluid Flowing Capacity in Gas Condensate Reservoirs

Abstract: It is well-known that the production of gas-condensate reservoirs is significantly affected by the liquid condensation near the wellbore region. Gas-wetting alteration can be one of the most effective approaches to alleviate condensate accumulation and improve liquid distribution. However, gas well deliverability is still limited because the wettability of cores is altered only from liquid-wetting to intermediate gas-wetting by using traditional chemical stimulation. To solve this bottleneck problem, herein, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 59 publications
(88 reference statements)
0
13
0
Order By: Relevance
“…The surface modification of MWCNTs has been described by previous papers in detail 17‐19 . The absorption peaks of OH stretch (carboxylic acids) and CO stretch appeared at 2923 and 1739 cm −1 for CNT‐COOH, while no obvious characteristic peaks were observed in IR curve for CNT 20‐21 . This indicates that the carboxyl group has been successfully grafted onto pure CNT after acidation modification.…”
Section: Resultsmentioning
confidence: 81%
“…The surface modification of MWCNTs has been described by previous papers in detail 17‐19 . The absorption peaks of OH stretch (carboxylic acids) and CO stretch appeared at 2923 and 1739 cm −1 for CNT‐COOH, while no obvious characteristic peaks were observed in IR curve for CNT 20‐21 . This indicates that the carboxyl group has been successfully grafted onto pure CNT after acidation modification.…”
Section: Resultsmentioning
confidence: 81%
“…On the former, lots of researches have been done to study the effect of different types of matrix or curing agents on the properties of SMPs. It was confirmed that molecular types do have important impact on performance of SMPs, and SMPs with excellent properties have been prepared and systematically studied 10 . For instance, the rigid structure containing benzene ring could be introduced to enhance mechanical strength of polymers, 11 or amine based curing agents with long aliphatic chains could be added to improve toughness 12 .…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the anti-corrosion of wellbore, pipelines and related facilities is a continuous task [3][4][5][6][7]. Most oil and gas wellbore and pipeline corrosion inhibitors need to be continuously injected into the fluid for corrosion inhibition, which requires additional work on the part of on-site operators [8][9][10]. One attractive anti-corrosion strategy is to modify the surfaces of wellbore and pipeline to make them have stable corrosion resistance during the production, while reducing the workload.…”
Section: Introductionmentioning
confidence: 99%